Education in International Islamic University Malaysia: the role of quality assurance exercises - Abdul Rahman, Shukran; Zubairi, Ainol Madziah (2011)
This paper presents an institutional level study of the International Islamic University Malaysia in its response to QA. It discusses the university’s responses to the exercise of quality assurance, and the important milestones in quality assurance exercises. It also outlines the quality assurance practices and their correspondence with the university’s mission, vision, and educational objectives. It also discusses theimportance of these exercises on various university activities, and the way forward for the university in substantiating its roles in higher education service.